APLIKASI COATING BERBASIS PEKTIN CINCAU HIJAU (Premna oblongifolia Merr.) PADA TELUR AYAM RAS - Vida Elsyana; Livia Rhea Alvita (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study was aimed to determine the effect of green cincau pectin concentration as a coating for broiler eggs and the length of storage time at room temperature on egg quality. The research was carried out in May-October 2021 at the Industrial Chemistry Laboratory and Agricultural Products Technology Laboratory, Lampung State Polytechnic. The experimental design used was a Factorial Completely Randomized Design (CRD) with 3 replications (triple). The factors studied were the concentration of green cincau pectin and storage time which consisted of several levels. The parameters measured were the percentage reduction in egg weight, yolk index, and Haugh Unit. The research data obtained were analyzed by means of variance (ANOVA) at a significance level of 5% and continued with Duncan's test. The results showed that there was an interaction (p<0.05) between the concentration of green cincau pectin and storage time on the percentage decrease in egg weight, yolk index, and Haugh Unit. The concentration of green cincau pectin showed a significant effect (P<0.05) on the percentage decrease in egg weight and Haugh Unit, but it was not significantly different (P>0.05) on the yolk index, while storage time resulted in a significant effect (P<0.05) on all test parameters. Green cincau pectin concentration 30% w/w tapioca as coating broiler eggs and stored for 6 days was the best combination treatment for the percentage reduction in egg weight, yolk index, and Haugh Unit. Key words: pectin, green cincau, coating, egg